2019
DOI: 10.1007/978-3-030-02487-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of an Operator Splitting Scheme for Abstract Stochastic Evolution Equations

Abstract: In this paper we study the convergence of a Lie-Trotter operator splitting for stochastic semi-linear evolution equations in a Hilbert space. The abstract Hilbert space setting allows for the consideration of convergence of the approximation for both the original and spatially discretized problems. It is known that the strong convergence of this scheme is classically of half-order, at best. We demonstrate that this is in fact the optimal order of convergence in the proposed setting, with the actual order being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…is problem can be viewed as a simplification of the internal combustion when dual ignition sparks are utilized [2,3]. e partial differential equation problem is first split to one-dimensional subproblems via exponential splitting and then Strategies 1 and 2 are applied, respectively [8,14,18].…”
Section: Simulation Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…is problem can be viewed as a simplification of the internal combustion when dual ignition sparks are utilized [2,3]. e partial differential equation problem is first split to one-dimensional subproblems via exponential splitting and then Strategies 1 and 2 are applied, respectively [8,14,18].…”
Section: Simulation Experimentsmentioning
confidence: 99%
“…Such a value T σ is called the quenching time which is a possible combustion-reaction time [7,8]. It has been shown that a necessary condition for quenching to occur is max 0≤x≤1 u(x, t) ⟶ 1 − , as t ⟶ T − σ .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers in numerical analysis have recently benefited from a surge of activities which overlaps with pure mathematical analysis (see, for instance, [3,6,15,16,24,26,28] and publications cited therein). Inspired by this fact and the recent works of Littlejohn and Wellman concerning the investigation of self-adjoint operators in extended Hilbert spaces (cf., e.g., [19,20,21]), in this article we consider so-called strongly continuous fractional semigroups in arbitrary normed vector spaces.…”
Section: Introductionmentioning
confidence: 99%